Developing and Profiling the Scientific Literacy Test Items on Prospective Science Teachers: A Focus on Health and Disease in Socioscientific Issues - Winata Tegar Saputra; Lilit Rusyati; Nuryani Y Rustaman; Indra Fardhani; Ismail Fikri Natadiwijaya (Universitas Pendidikan Mandalika, 2026)
This study aimed to develop scientific literacy instruments aligned with the 2025 framework, focusing on socioscientific issues (SSI) related to health and disease, and apply them to prospective science teachers (PSTs). Despite the updated framework, many Indonesian scholars still use outdated models. Using an exploratory sequential mixed-methods design and the ADDIE model, this research involved 194 PSTs, three assessment experts, and two content experts. Textbook analysis revealed that competency 1 was most dominant, while competency 3 was the least addressed in both books and classroom practice. The instrument development process began with 30 items and underwent multiple stages, including expert validation, readability checks, pilot testing, and statistical analyses of reliability, item difficulty, and discrimination. Ultimately, 23 items were validated with high reliability (0.92) and a balanced difficulty range that cover the cognitive skills such as content, procedural, and epistemic knowledge. A profiling analysis using these items showed that most PSTs demonstrated moderate scientific literacy, with third-year students outperforming first- and second-year students. Overall, the instrument proved effective, as it was systematically developed based on textbook analysis and teacher interviews to reflect current scientific literacy demands, particularly in preparation for PISA 2025. This instrument also expects the PSTs in the future to have the ability to teach their students about the skills of the content, procedural, and epistemic knowledge.